Metodologi penelitian : (petunjuk praktis untuk pemecahan masalah bisnis, penyusunan skripsi, tesis dan disertasi) / H. Hapzi Ali, H. Nandan Limakrisna - HAPZI ALI , H. , 1966-; Nandan Limakrisna , H. (Deepublish, 2013)
x, 184 hlm. : ilus. ; 25 cm